2017
DOI: 10.1111/ceo.12982
|View full text |Cite
|
Sign up to set email alerts
|

PAX6 allelic heterogeneity in Mexican congenital aniridia patients: expanding the mutational spectrum with seven novel pathogenic variants

Abstract: The mutational diagnostic rate in this series was 77%, which is comparable with reports from other populations. Importantly, no founder mutations were identified in this case series. Our results add 7 novel PAX6 pathogenic variants to the aniridia-related mutational spectrum and reveal considerable PAX6 allelic heterogeneity in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…One of the previously identified variants, c.140A>G, was described as a missense variant p.(Gln47Arg) located within the PAX6 DNA-binding paired domain (PD) and affects its function [14,15]. In the present study, we showed that the functional effect of this SNV is a consequence of splicing disruption rather than a dysfunctional protein.…”
Section: Discussionmentioning
confidence: 51%
“…One of the previously identified variants, c.140A>G, was described as a missense variant p.(Gln47Arg) located within the PAX6 DNA-binding paired domain (PD) and affects its function [14,15]. In the present study, we showed that the functional effect of this SNV is a consequence of splicing disruption rather than a dysfunctional protein.…”
Section: Discussionmentioning
confidence: 51%
“…In Patient 2, the mutation c.718C>T (p.Arg240X) in exon 9 has been consistently reported according to LOVD. Another mutation c.718delC at this site has been reported recently ( 26 ). These two mutations are predicted to result in a premature stop codon and produce a truncated PAX6 protein.…”
Section: Discussionmentioning
confidence: 76%
“…The c.183C˃G found in the proband from Family 2 results in premature insertion of a stop codon, p.(Tyr61*). This variant has been previously reported in one sporadic case with aniridia (Perez-Solorzano et al, 2017). As it was not present in either parent and paternity testing was performed, we have considered it to be de novo.…”
Section: Molecular Genetic Analysismentioning
confidence: 95%